Nigeria And The Petroleum Resource Curse: What Ghana Can Learn For Improved Management Of Oil And Gas Revenues. (Global Journal of Human-Social Science, 2012)
Nigeria discovered oil and gas resources in 1956 and has had poor economic performance and even civil war between 1967 and 1970 The recent discovery of petroleum resources in Ghana is one of the positive shocks that country has experienced in the recent past How this initial positive shock is converted into durable all round development benefits is argued in this paper to be a matter of policy Unlike Nigeria Ghana has an added advantage It can learn from other countries experiences notably Nigeria and Angola and make better policies to ensure economic growth and sustainability Casual observation tends to assume that the exploitation of natural resources such as Oil lead to an increase in income with positive knock on effects to poverty reduction However research shows that developing African countries that have at least 25 percent of their exports from natural resources are more likely to have conflicts Resource conflicts seem to be driven by poor governance greed and corruption Improved governance of income from petroleum resources in Ghana could reduce the risk of conflict in Ghana provided Ghanaian government is ready to learn from Nigerian s bitter experiences Collier 2005 argues that conflicts prone countries are more likely to poorly convert their income from natural resources into growth and revenue He opines that revenue from primary commodities is a risk factor in civil war This paper argues that Ghana should subscribe to the principles of good governance Improved governance will help to reduce both domestic as well as regional conflict risks
Keywords: Petroleum resource curse; oil revenue; conflict and management